Incidence of seed-borne fungi of stored sunflower seeds (Helianthus annuus) in Tanzania and their influence on seed viability and vigor - Siwajali Selemani; Richard Madege; Yasinta Nzogela (Frontiers in Sustainable Food Systems)
Understanding the impact of seed-borne fungi on seed quality is crucial for improving sunflower productivity. This study was conducted to investigate the incidence of seed-borne fungi in stored sunflower seeds under ambient conditions and their effects on seed viability and vigor. Certified seeds, quality-declared seeds (QDS), and farmer-saved seeds (FSS) were stored for 6 months, with monthly sampling to evaluate fungal infection percentage (FIP), germination percentage (G), and seedling vigor index (SVI). Key findings include the identification of fungal species: Aspergillus flavus, A. niger, Alternaria padwickii, A. zinniae, Botrytis cinerea, Curvularia lunata, Fusarium vericillioides, and Rhizopus arrihizus. The highest incidence of F. vericillioides (14.39%) and B. cinerea (14.28%) occurred in FSS, while the lowest incidence of A. zinniae (1.83%) was recorded in QDS. Total fungal infection was highest in FSS (73.11%) compared to QDS (66.94%) and certified seeds (67.06%). Seed quality parameters showed a clear trend: QDS exhibited the highest G (81.56%), with certified seeds following closely (81.33%). The highest SVI was recorded in certified seeds (96.76), with QDS showing a similar result (95.69). In contrast, FSS showed the lowest G% (60.67) and SVI (65.98). Seeds with minimal fungal infection consistently demonstrated higher G% and SVI. These results highlight the detrimental impact of fungal infections on seed vigor and viability. This study is the first in Tanzania to report and quantify the incidence of seed-borne fungi in stored sunflower seeds, providing critical insights for improving seed management practices and sunflower production.